2007
DOI: 10.1007/s10384-007-0467-9
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Contrast Sensitivity Function and Ocular Higher Order Aberration by Conventional Myopic Photorefractive Keratectomy

Abstract: PRK significantly increases ocular higher order aberrations, which compromise contrast sensitivity function after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 29 publications
2
14
0
Order By: Relevance
“…This change was greater than in our study, in which the Strehl ratio decreased by a factor of 1.10 in the PRK group and 1.07 in the LASIK group; this could be attributed to the shorter postoperative period in the study by Marcos. Sakata et al 33 also found that PRK significantly reduced the area under the contrast sensitivity function by a factor of 1.07 on average, which fairly correlates with the MTF findings in our study.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This change was greater than in our study, in which the Strehl ratio decreased by a factor of 1.10 in the PRK group and 1.07 in the LASIK group; this could be attributed to the shorter postoperative period in the study by Marcos. Sakata et al 33 also found that PRK significantly reduced the area under the contrast sensitivity function by a factor of 1.07 on average, which fairly correlates with the MTF findings in our study.…”
Section: Discussionsupporting
confidence: 94%
“…There have been several attempts to assess aberrations in eyes that have had PRK and LASIK using this technique. In general, the results showed significantly more HOAs after PRK and LASIK, 14,[24][25][26][27][28][29][30][31][32][33] although in general, no significant differences between the techniques were observed. 14,25 Retinal image quality can also be clinically assessed with instruments based on the double-pass technique.…”
mentioning
confidence: 98%
“…However, refractive procedures also inevitably alter corneal SA and the extent of the change varies by procedure. Some reports have found that laser in situ keratomileusis (LASIK) and photorefractive keratectomy (PRK) procedures tended to increase postoperative corneal SA, but to varying extents [4-7]. After myopic correction, corneal SA changed to a more positive value [7], while after hyperopic correction, corneal SA changed from a positive to a negative value [8].…”
mentioning
confidence: 99%
“…These results indicated that the centration errors exerted a significant influence on the residual wavefront aberrations [8]. Decentrations during refractive surgery may account for a portion of the postoperative increases in higherorder aberrations [9,10]. On the other hand, lateral decentration produced significantly greater residual higher-order aberrations RMS values than cyclotorsional misalignment during wavefront-guided excimer laser corneal ablation [11].…”
Section: Introductionmentioning
confidence: 65%